The lives and work of Bob Dylan. Issue 2 (May 2022) - Frith, Simon
Abstract : According to the website Come writers and critics, which keeps a running list of all 'documents related to Bob Dylan printed on paper', by the end of 2021 (Dylan's 80th year), there were 829 books about him in English and 723 in 36 other languages (from 175 in German to one each in Bulgarian and Vietnamese). 1 The list is indiscriminate in terms of the various books' quality, originality or readability, but looking at the bibliographies of the various works I'm reviewing here, it seems that there are at least 50 Dylan books that academic Dylanologists take seriously (and many more journal articles). 2 From this perspective, my four titles provide a useful cross-section of the most common academic Dylan studies in disciplinary terms: biography, literary criticism, musicology and cultural studies. I should also note that in March 2016 the George Kaiser Family Foundation bought Bob Dylan's personal archive (for $22 million according to Heylin) and gave it a permanent home in Tulsa. This has opened up significant new research possibilities. In its own words: The Bob Dylan Archive ® highlights the unique artistry and worldwide cultural significance of Bob Dylan. Housed at the University of Tulsa's Helmerich Center for American Research at Gilcrease Museum, the archive includes decades of never-before-seen handwritten manuscripts, notebooks and correspondence; films, videos, photographs and artwork; memorabilia; personal documents; unrecorded song lyrics and chords. Like the writer and composer archives to be found in many university libraries, the Bob Dylan collection is accessible onsite (and by appointment) to 'individuals with qualified research projects', and The World of Bob Dylan is, in effect, a celebration of a new era for Dylan scholarship. Its editor, Sean Latham, is the Director of the related Institute for Bob Dylan Studies. 3 However, the first book to draw on the Bob Dylan Archive systematically is Clinton Heylin's The Double Life .